Activated Carbon: Eco-friendly Material for Wastewater Application - Siti Suhana Hassan, Siti Suhana; Heng, Yen Khong; Chang Robin Yee Hui, Chang Robin Yee Hui (UiTM Press, 2022)
With the advancements of technologies, pollution is worsening day by day, especially water pollution. Water pollution was caused by the excess discharge of the toxic substances that enter the water bodies such as lakes, ponds, and streams. The toxic substances that accumulate in the water sources can be harmful for the living. This water is not safe for public use and requires treatments before it is disseminated for household use. As such, activated carbon is a powerful adsorbent in wastewater treatments. Production of activated carbon from agricultural sources has attracted the researcher’s attention. Since agricultural sources are high in availability due to their abundance, low-cost operation, and eco-friendly materials. Activated carbon can remove various dyes including methylene blue, Rhodamine B, methyl orange, aniline yellow, and Remazol brilliant blue R in wastewater discharge from the industries. Activated carbon is also a powerful adsorbent for heavy metals such as Pb (II), Co (II), Ni (II), Zn (II), Cu (II), Cd (II), Mn (II), Hg (II) and As (V). Besides, activated carbon can act as an adsorbent for the removal of common pharmaceutical waste and phenolic compound of 2,4-dimethylphenol.